Analisis Penyebab Ketidaksesuaian Akurasi Stok pada PT. X - Mariska, Dewi Refi; Wati, Putu Eka Dewi Karunia (Fakultas Teknik UMRI, 2025)
PT. X is a leading ceramic tile manufacturer in Indonesia, with three main production facilities located in Surabaya, Gresik, and Bekasi, and warehouses located in Bali, Bandung, Jakarta, and Medan. This research aims to analyze and identify the impact of warehouse stock accuracy on the company’s operational needs. Stock accuracy also aims to identify the main factors that significantly contribute to inventory discrepancies in PT. X's warehouses and to formulate improvement strategies as recommendations that can be implemented to increase stock accuracy and achieve the goals set by the company in supporting overall warehouse operational effectiveness. This study uses the Root Cause Analysis method to identify and analyze the factors that are parameters of low stock accuracy in the warehouse, with the support of 5W+1H, Fishbone Diagram, and Pareto Diagram analyses to determine the root causes in detail. The findings of this study can be used as a basis for decision-making related to warehouse stock policies, stock opname scheduling, and improving stock accuracy.